If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n + 3 = 6n + -9 Reorder the terms: 3 + 5n = 6n + -9 Reorder the terms: 3 + 5n = -9 + 6n Solving 3 + 5n = -9 + 6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6n' to each side of the equation. 3 + 5n + -6n = -9 + 6n + -6n Combine like terms: 5n + -6n = -1n 3 + -1n = -9 + 6n + -6n Combine like terms: 6n + -6n = 0 3 + -1n = -9 + 0 3 + -1n = -9 Add '-3' to each side of the equation. 3 + -3 + -1n = -9 + -3 Combine like terms: 3 + -3 = 0 0 + -1n = -9 + -3 -1n = -9 + -3 Combine like terms: -9 + -3 = -12 -1n = -12 Divide each side by '-1'. n = 12 Simplifying n = 12
| Y=x+2x-3 | | 6-(3x-4)+7x-4= | | 2m+4(m-2)=28 | | -3+4-20x=19 | | 4w-2(1+w)=-38 | | (4y+9)-(4y-4)= | | 2m-4=8(m+4) | | 5y+38+42=180 | | 15w-12=-111 | | n^2+9x+20= | | .33+.66=.66m-.66 | | 2(m+3)-1=11+2m | | 8m-3m+10= | | 15in=5x+12x+13x | | [2x+8]=3X+7 | | -3+4(1-5d)=19 | | 2(m+3)-11=11+2m | | 6x+2-(-2x)=x+5-(-5) | | 3(5x-9)=-16(7-x) | | 25t^3-16t=0 | | 7s^2-6s-16=0 | | 6c-4+2c-7= | | 30x-15x^2=0 | | x(x-7)=14 | | 23=46c | | -3.6=-2f | | -7n+4+6=27 | | 4a-5= | | 4x+2=2x^2 | | -3.6=-2 | | -3(2t+5)=2(5t+7) | | 3|4x+6|=24 |